Wacana Kecantikan dan Kekerasan: Membaca Novel “Cantik Itu Luka” Karya Eka Kurniawan Perspektif Michel Foucault: Discourse on Beauty and Violence: Reading Eka Kurniawan's Novel "Beauty is a Wound" from Michel Foucault's Perspective - Nilna Sifaana; Mohamad Hudaeri; Agus Ali Dzawafi (Jurnal Filsafat Indonesia, 2026)
Abstract This research begins with the issue of the representation of beauty, which is often associated with the practice of violence against women. In Eka Kurniawan's novel Cantik Itu Luka, beauty is not positioned as something neutral, but rather presents as a discourse that normalizes women's bodies while simultaneously opening up opportunities for subjugation and violence. Based on these problems, this study aims to uncover how the discourse of beauty is constructed in the text, how this construction is related to the practice of violence, and how the female body is represented as a locus of power and a space of resistance. This research uses a qualitative-descriptive method with a literary discourse analysis approach. The research data consists of narrative excerpts, character descriptions, and events in the novel, which are analyzed through Michel Foucault's theoretical framework, specifically the concepts of power-knowledge, discourse, and the body. The results show that beauty functions as a mechanism of power that disciplines women's bodies, trapping them in colonial and patriarchal domination, and giving rise to various forms of physical and symbolic violence. However, the novel also presents a representation of resistance through characters who refuse to submit to the dominant discourse of beauty. The conclusion of this study confirms that Cantik Itu Luka reflects the power relations over women's bodies, which remain relevant to contemporary phenomena related to beauty standards, gender-based violence, and women's resistance.